Implementation of business intelligence in an IT organization: The concept of an evaluation model - Tomasz Sitek; Michal Litka (Foundations of Management, 2013)
This paper presents the issue of assessing the validity and effectiveness of implementing a Business Intelligence system in an IT Support Organization. This entity provides IT services to external clients involving, in particular, the storage and processing of large amounts of data. The vast amount of realized projects and also incidents reported in connection with those projects prevented effective decisions from being made without the support of dedicated technologies. The authors present the problems encountered by the studied entity and describe the tool that was selected to improve the situation. The aim of this study is to measure and describe the key processes in the organization on the basis of prepared aggregated measures, first prior to the implementation of the BI system and then a year after its implementation. The evaluation model developed by the authors allowed the assessment of the key aspects of the company's operation over 2 years. It thus helped decision makers to establish whether the decision to implement the Business Intelligence system was correct or not.
Keywords: 650; Business Intelligence; IT support organization; decision-making; evaluation model